Looks good for hockey - Calder, S. (Sportscience)
As part of her PhD work, author has compared two visual training programs for their effects on performance in hockey. The first was a generic visual skills-training program, and the other combined this program with a sport-specific visual awareness coaching program. I'll describe these two programs, then tell you how they worked. These results appear to be clear cut and exciting. At the elite level, improvements in performance with any type of training are few and far between. It looks like combining a general eye-function program with coaching sport-specific visual awareness is a winning combination. Four weeks of normal training in elite hockey players produced improvement in three of 22 skill tests. A standard visual-skills program on top of normal training improved performance of nine of the 22 tests, and when visual "awareness" coaching was also added, performance improved in 16 tests.